SISTEM INFORMASI PEMERINTAHAN DESA PADA KANTOR DESA TENGGIR PANJI SITUBONDO MENGGUNAKAN PHP DAN MYSQL - Yuni Nur Waqiah (Department of Science and Technology Ibrahimy University, 2018)
The Tenggir Village Office is a government agency engaged in public services that has a good management system. That can be seen from the service to the community, the better. With more and more people, while the problem faced by the agency is managing data that is still less effective, one of which is the management of mail-making services. Management services for writing letters at institutions using computerized systems that are not easy to manage, such as using Microsoft Word. The development of information from the old system to the new system is expected to help the institution, storage, and archiving reports more easily. The design and implementation of the Village Administration Information System at the Tenggir Panji Situbondo Village Office use the PHP programming language and the MySQL database and other software in the design of this system. In its implementation, this application can answer information needs that can be used for financial management easier and faster, especially for reporting.